EVALUATION OF ANTIOXIDANT ACTIVITY IN OAK LEAVES FROM THE REPUBLIC OF MOLDOVA EXPOSED TO HEAT STRESS - Petru CUZA (Journal of Plant Development)
The total activity of antioxidant substances, oxidases, and catalases was evaluated in the leaves of three oak species – pedunculate oak (Quercus robur L.), sessile oak (Q. petraea Liebl.), and downy oak (Q. pubescens Willd.) from the Republic of Moldova, subjected to thermal shock at 50 °C for durations of 20, 40, and 60 minutes. The study aimed to identify variations as well as common and divergent responses of these species according to ecological zone, thermal shock duration, and recovery period, in order to assess their thermotolerance and specific adaptations to environmental conditions. The results showed that during the recovery period, leaves of pedunculate oak and downy oak from the center and southern regions, as well as sessile oak from the center region, exhibited high total antioxidant activity. Additionally, pedunculate oak and sessile oak from the center and southern regions displayed increased oxidase activity, while sessile oak from the center region demonstrated high catalase activity, indicating the activation of adaptive processes to thermal shock. Conversely, pedunculate oak and sessile oak from the northern region exhibited a decrease in total antioxidant and oxidase activity during the recovery period, suggesting an increase in leaf thermotolerance. Moreover, the downy oak from the northern region demonstrated an increase in thermotolerance, reflected in the activity of all types of antioxidant substances after extended recovery periods. The study demonstrated that the investigated oak species enhance their thermotolerance in the northern region by developing specific adaptive strategies to thermal shock. These oak species adjust their antioxidant and enzymatic activity in accordance with the specific environmental conditions of the ecological zone in which they grow.